HSPA1A, HSPA1L and TRAP1 heat shock genes may be associated with prognosis in ovarian epithelial cancer - De Andrade, Warne Pedro [UNESP]; Braga, Leticia Da Conceicao [UNESP]; Goncales, Nikole Gontijo; Silva, Luciana Maria; Da Silva Filho, Agnaldo Lopes [UNESP] (Spandidos Publ Ltd, 2020)
Epithelial ovarian cancer (EOC) is the most lethal gynecological malignancy, with the presence of chemoresistance contributing to the poor prognosis. Heat Shock Proteins (HSPs) genes are activated in response to pathophysiological stress and serve a role in a variety of stages in carcinogenesis, acting primarily as anti-apoptotic agents and in chemotherapy resistance in a variety of tumor types. The current study evaluated the HSP gene expression profile in women with ovarian cancer (OC) and their correlation with clinical and pathological aspects of patients with OC. A total of 51 patients included in the current study were divided into four groups: Primary Epithelial Ovarian Cancer (EOC; n=14), metastatic EOC (n=11), ovarian serous cystadenoma (n=7) and no evidence of ovarian malignancy or control groups (n=19). RNA extraction and reverse transcription-quantitative (RT-q) PCR was then performed on the samples obtained. RT-qPCR was performed to compare TNF receptor associated protein 1 (TRAP]), heat shock protein family (HSP) HSPB1, HSPD1, HSPA1A and HSPA1L expression in primary and metastatic EOCs. TRAP], HSPB1, HSPD1, HSPA1A and HSPAlL gene expression did not differ among groups. HSPA1A, HSPA]L and TRAP] were revealed to be underexpressed in the primary and metastatic EOC groups, with HSPA1L exhibiting the lowest expression. TRAP] expression was higher in tumors at stages I/II compared with those at stages III/IV. No correlation was exhibited between HSP expression and age, menarche, menopause, parity, period after menopause initiation, cytoreduction, CA-125 or overall and disease-free survival. HSPA1A was negatively correlated with the risk of mortality from OC. The results indicated that the downregulation of HSPA1A, HSPA1L and TRAP] could be associated with the clinical prognostic features of women with EOC.
Keywords: ovarian cancer; prognosis; resistance to chemotherapy; heat shock proteins; gene expression